CORRELATION OF SONOGRAPHIC OPTIC NERVE SHEATH DIAMETER WITH OPENING PRESSURE ON LUMBAR PUNCTURE IN PATIENTS OF IDIOPATHIC INTRACRANIAL HYPERTENSION - Ahmad, Sajjad; Noor Ul Hussain; Mian Iftikhar ul Haq; Haider Ali Khattak; Asghar Ali (Journal of Ayub Medical College Abbottabad, 2024)
Background: Evaluation of opening pressure (OP) of CSF on lumbar puncture (LP) is an invasive procedure for the confirmation of diagnosis of idiopathic intracranial hypertension (IIH). Sonographic optic nerve sheath diameter (ONSD) measurement is a non-invasive method which can help in the estimation of intracranial pressure (ICP). The study was carried out to find out the correlation between ONSD and OP on LP in patients of IIH. Methods: The Cross-sectional study was hosted by medical teaching institute, Gajju medical college, Swabi and Frontier institute of Ophthalmology, Peshawar, from 1st June, 2021 to 31st May, 2023.Total participants were 50, 25 in Group A having diagnosis of IIH and 25 in Group B as control group from general population. The patients in Group A had ONSD assessment followed by measurement of OP and then the process was repeated at two weeks follow up. Participants in Group B had only one assessment of ONSD. Correlation between ONSD and OP was determined. Best cut-off-value for raised ICP was calculated. Results: The mean ONSD was 5.91±0.63 in Group A and 5.07±0.50 in Group B (p=0.00). The mean OP in Group A was 31.64±3.81 cm H2O initially. The mean ONSD and OP at follow up were 5.18±0.42 and 19.64±3.52 cm H2O respectively. The best cut-off-value was 5.60 mm of ONSD for estimation of raised ICP (sensitivity 88% and specificity 88%). Conclusion: Sonographic ONSD has a positive correlation with OP on LP in IIH patients and can be used as a non-invasive tool for the assessment of ICP in IIH patients.